Onicodistrofia lupoide simétrica canina: relato de caso - Palumbo, Mariana Isa Poci; Machado, Luiz Henrique de Araújo [UNESP]; Soares, Luciana Murai; Torres Neto, Rafael; Fabris, Viciany Erique; Lourenço, Maria Lucia Gomes [UNESP]; Vailati, Maria do Carmo Fernades (My University, 2010)
Symmetric lupoid onychodystrophy, or lupoid onychitis, is a multifactor immune-mediated onychopathy. The aim of the present study is to report the occurrence of lupoid onychitis in a two year-old mongrel dog helped at the Small Animal Dermatology Service of Sao Paulo State University Veterinary Hospital, in Botucatu, São Paulo. The animal presented lameness, onycholysis in five digits, paronychia, onychomadesis, nail softening and leuchonychia, as well as melicerous crusts in interdigital spaces and nailbeds. No non-dermatological systemic symptoms were observed. Complementary exams were negative for parasites or fungi. After 15 days of treatment there was partial recovery followed by recurrence. Onychectomy was performed in two digits for histopathological examination and fungal culture, which was negative. Histopathology was consistent with lupoid onychitis, reinforcing the importance of this complementary exam.

La onicodistrofia lupoide simétrica u oniquitis lupoide, es una onicopatía inmunomediada de etiología multifactorial. Nuestro objetivo es reportar la presencia de oniquitis lupoide en un perro atendido en el sector de Dermatología de la FMVZ/Unesp, de Botucatu. El animal presentaba claudicación y onicolisis en cinco dígitos, paroniquia, onicomadesis, onicomalacia y leuconiquia, además de costras melicéricas en los espacios interdigitales y lechos ungulares. No había ninguna alteración sistémica ni dermatológica. Los exámenes complementarios fueron negativos. Hubo mejora parcial después de 15 días de tratamiento, con reincidencia posterior. Fue entonces que se realizó oniquectomia en dos dedos, para examen histopatológico y para cultivo fúngico, siendo este último negativo. Los cortes histológicos fueron compatibles con oniquitis lupoide, demostrando la importancia de este examen complementario

A onicodistrofia lupoide simétrica, ou oniquite lupoide, é uma onicopatia imunomediada de etiologia multifatorial. Nosso objetivo é relatar a ocorrência de oniquite lupoide em um canino atendido no Serviço de Dermatologia Veterinária do Hospital Veterinário da FMVZ/Unesp de Botucatu. Este apresentava claudicação e onicólise em cinco dígitos, observando-se paroníquia, onicomadese, onicomalácia e leuconíquia, além de crostas melicéricas em espaços interdigitais e leitos ungueais. Não havia qualquer alteração sistêmica não dermatológica. Os exames complementares foram negativos. Após quinze dias de tratamento, houve melhora parcial, com recorrência posterior. Realizou-se então uma onicoectomia em dois dedos, para exame histopatológico e cultivo fúngico, este último resultando negativo. Os cortes histológicos foram compatíveis com oniquite lupoide, demonstrando a importância desse exame complementar.
Canine symmetrical lupoid onychodystrophy - case report
Onicodistrofia lupoide simétrica canina - reporte de caso
Keywords: Dogs; Immune-mediated dermatitis; Onychitis; Perros; Dermattitis inmunomediada; Oniquitis; Cães; Dermatite imunomediada; Oniquite